2011
DOI: 10.1029/2010gb003864
|View full text |Cite
|
Sign up to set email alerts
|

ThepCO2in boreal lakes: Organic carbon as a universal predictor?

Abstract: [1] During the past two decades, it has become evident that a majority of lakes are net conduits of CO 2 to the atmosphere. This insight has implications both for lake metabolism per se and for assessing the role of lakes in the global C cycle. The concentration of dissolved organic carbon (DOC), which constitutes >90% of the total organic carbon (TOC), has been identified as a key driver of partial pressure of CO 2 (pCO 2 ). A crucial question is whether one may identify global relationships in the DOC-pCO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 36 publications
2
47
2
Order By: Relevance
“…1300 m) than lakes in our study (cf. Table 1), Larsen et al (2011) found TOC concentration (range 0.25-24.5, mean 3.9 mg L 21 ) to be the best predictor (R 2 5 0.73) of partial pressure of carbon dioxide (P CO 2 ), but lake area as a single predictor did not explain the variability of P CO 2 . We found a strong relationship between CH 4 and CO 2 concentrations and lake-area-related stability, especially during the summer stratification in the lakes located in the boreal forest area in a flat landscape (maximum altitude difference , 71 m).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1300 m) than lakes in our study (cf. Table 1), Larsen et al (2011) found TOC concentration (range 0.25-24.5, mean 3.9 mg L 21 ) to be the best predictor (R 2 5 0.73) of partial pressure of carbon dioxide (P CO 2 ), but lake area as a single predictor did not explain the variability of P CO 2 . We found a strong relationship between CH 4 and CO 2 concentrations and lake-area-related stability, especially during the summer stratification in the lakes located in the boreal forest area in a flat landscape (maximum altitude difference , 71 m).…”
Section: Discussionmentioning
confidence: 99%
“…The significant correlation between CO 2 and TOC concentrations has been reported for several lakes and regions, but the variance of CO 2 explained (R 2 ) by TOC or dissolved organic carbon has varied from , 10% (Kortelainen et al 2006) up to 70% (Larsen et al 2011). In 112 Norwegian lakes sampled in October and located within a greater range of altitude (.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patterns suggest that the net metabolic balance of freshwater ecosystems is not only related to their nutrient and organic matter inputs, but also to the nature of dominant pools of organic carbon that are consumed and respired by pelagic bacteria. Knowledge of the character of these pools may, in turn, contribute to understanding of why lakes in different regions differ in their relationships between DOC and pCO 2 (Larsen et al, 2011). The fundamental role of substrate control of bacterial RQ and community metabolism was further highlighted by the Biolog results, showing that bacterial communities in high RQ systems were characterized by their capacity to degrade oxidized organic acids, whereas communities in low RQ systems were optimized for degrading reduced compounds, such as lipids (Figure 4c).…”
Section: Discussionmentioning
confidence: 99%
“…DOC thus has negative impacts on primary producers both by competing for photons and by stimulating their major nutrient competitors. Increased levels of terrestrially-derived DOC in concert with reduced availability of inorganic phosphorus in lakes may shift systems further towards net heterotrophy and thus a net CO 2 release (Sobek et al 2003;Larsen et al 2011c).…”
Section: Greenhouse Gases and Heterotrophymentioning
confidence: 99%